Pulmonary hypertension in the premature infant population: Analysis of echocardiographic findings and biomarkers. Issue 3 (23rd November 2017) - O'Connor, Michael G.; Suthar, Divya; Vera, Kimberly; Slaughter, James C.; Maitre, Natalie L.; Steele, Steven; Beller, Amy; Fike, Candice D.; Aschner, Judy L.; Moore, Paul E.; Austin, Eric D.
Abstract: Objective: Extremely low gestational age neonates (ELGANs) are at risk for pulmonary hypertension (PH). We hypothesized that PH, defined by echocardiogram at 36 weeks gestational age (GA), would associate with respiratory morbidity, increased oxidant stress, and reduced nitric oxide production. Study Design: ELGANs in the Vanderbilt fraction of the Prematurity and Respiratory Outcomes Program (PROP) who had echocardiograms at 36 ± 1 weeks GA were studied. Echocardiogram features of PH were compared with clinical characteristics as well as markers of oxidant stress and components of the nitric oxide pathway. Biomarkers were obtained at enrollment (median day 3), 7, 14, and 28 days of life. Results: Sixty of 172 infants had an echocardiogram at 36 weeks; 11 had evidence of PH. Infants did not differ by PH status in regards to demographics, respiratory morbidity, or oxidant stress. However, odds of more severe PH were significantly higher in infants with higher nitric oxide metabolites (NOx) at enrollment and with a lower citrulline level at day 7. Conclusions: Respiratory morbidity may not always associate with PH at 36 weeks among ELGANs. However, components of nitric oxide metabolism are potential biologic markers of PH in need of further study.